1993
DOI: 10.1103/physrevlett.71.2252
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous behavior of the vibrational spectrum of the high-pressure δ phase of nitrogen: A second-order transition

Abstract: Anomalous behavior of the vibrational-spectrum of the high-pressure delta-phase of nitrogen : a second-order transition Scheerboom, M.I.M.; Schouten, J.A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…In accordance with the results of Ref. 4, Westerhoff et al 5 have found an anomaly in the pressure dependence of the linewidth of the 1 vibron, which corresponds to the a sites, at a pressure of 12 GPa at room temperature.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In accordance with the results of Ref. 4, Westerhoff et al 5 have found an anomaly in the pressure dependence of the linewidth of the 1 vibron, which corresponds to the a sites, at a pressure of 12 GPa at room temperature.…”
Section: Introductionsupporting
confidence: 79%
“…For the xϭ0.75 we estimate the temperature of the break to be 0 to 30 K above the second order transition temperature of pure N 2 . 4 No additional Raman peaks have been observed near the break. Since the frequencies have been measured in temperature steps of about 10 K and considering the accuracy, a small hysteresis of a few K cannot be excluded.…”
Section: B Second Order Transitionmentioning
confidence: 97%
“…The splitting of the frequency of the molecules at the disks sites at low temperature, caused by the difference in localization, has not been reported in Ref. 18. This might be due to the experimental resolution, but needs further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…Scheerboom and Schouten 18 observed that the linear behavior of 2 of the ␦ loc structure is slightly steeper than that of the ␦ rot structure ͑Fig. 3͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation